LITHOLOGIC FEATURES OF THE LOWER CRETACEOUS ROCKS OF NORTH-WESTERN BLACK SEA SHELF - RIABUKHA, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Information about variety of The Lower Cretaceous sediments of north-western Black Sea shelf is set in. The detailed sediment description of the South Golitsinske, Illichivske, Odeske, Olimpyske, Desantne, Fedrivske, Gamburtzeva, Flangove, Bezimenne sections is given. Basically the section is presented by carbonate deposit, but sandstones, siltstones, mudstones and volcanic tuffs are found too. It is possibly making of the Lower Cretaceous combined section based on data comparison from different areas.